PENGARUH TECHNOLOGY ACCEPTANCE TERHADAP USER EXPERIENCE DALAM PENGGUNAAN SMARTPHONE - Lilis Ratnasari; Ursa Majorsy (Jurnal Sosial Humaniora dan Pendidikan, 2022)
There are many factors that cause someone to tend to like and choose a smartphone brand to use. The selection of certain smartphone brands is related to consumer loyalty, one of which is influenced by the user experience quality factor of the smartphone that has been used and is an important consideration for switching or making choices on smartphone products from the same brand. To get a high user experience, a positive attitude on smartphones is needed. This study aims to examine the effect of attitudes on smartphones on user experience in the use of the gadget. The sampling technique used was random sampling, and the samples of this study are men and women who actively use smartphones. Data analysis in this study used path analysis. The results of the analysis concluded that the model fit with P=0.209 and GFI = 0.967.